IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KOLEKSI DIGITAL PADA KOLEKSI REPOSITORI KEMENTERIAN PERTANIAN - Nizahabila, Deira; Rizal , Edwin; Yanto, Andri (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
PUSTAKA Bogor is one of the libraries that has a collection of local content in digital form which can be accessed through a repository called the Ministry of Agriculture Repository. The collections contained in the Ministry of Agriculture's repository are publications from the Ministry of Agriculture, which makes the collections therein unique, specific collections and not found in other institutions. In order to realize PUSTAKA Bogor's goal of disseminating agricultural science and technology information, it is important to develop digital local content collections in the Ministry of Agriculture's repository. Collection development activities have a big influence on the service quality indicators in the library as a whole. Adapting to technological developments and the diversity of library collection media, collections in forms other than print, such as digital collections, also need to be developed in accordance with the policies set by PUSTAKA Bogor and the Ministry of Agriculture. This research aims to explain the form of implementation of collection development policies in the Ministry of Agriculture repository managed by PUSTAKA Bogor. This research uses a qualitative research method with a case study approach. Determining informants in this study used a purposive sampling technique which was adapted to the research topic. Data collection was carried out by observation, interviews and documentation. The results of this research are a form of implementation of collection development in the Ministry of Agriculture repository carried out through data entry using two methods, namely the conventional method carried out by the library and the harvesting method carried out by IT.